Drilling of a 2000-metre (6562-FT) Borehole for Geothermal Steam in Iceland - Ragnars, K.; Benediktsson, S. (Geothermal Energy Program (U.S.), 1981)
Drilling for geothermal heat has been carried out in Iceland since 1928, when hot water was obtained for district heating in Reykjavik. From that time, in particular in the sixties, extensive drilling has resulted in the annual utilization of 54 million tons of water and 2 million tons of steam. Five drilling rigs are used for geothermal drilling, with depth capacity ranging from 400 to 3,600 meters (1,312 to 11,812 feet). Drilling procedures vary extensively and depend on whether a high- or low-temperature field is being drilled, the main difference being the well-casing program and the blowout equipment used.